(untitled) (Swiss Medical Weekly, 2025)
STUDY AIMS: Higher surgeon volume has been correlated with improved therapy outcomes following total hip arthroplasty, and many countries have implemented minimum volume standards as a precondition for claiming reimbursement. However, there are large differences between healthcare systems worldwide and the applicability of international studies to a particular local healthcare environment may be limited. The aim of this study was to assess the relationship between surgeon case load (= number of procedures per year) and short-term revision rates (within two years of the index procedure) in patients undergoing primary total hip arthroplasty for hip osteoarthritis in a nationwide, registry-based study. In addition, the effects of increasing minimum volume standard thresholds on the potential reduction of the revision burden was simulated. METHODS: All patients registered in the Swiss National Joint Registry (SIRIS) for undergoing primary total hip arthroplasty for hip osteoarthritis between 2015 and 2021 were considered. Patients were aggregated according to the lead surgeon’s individual code. Surgeons lacking five years of uninterrupted practice were excluded. Multiple logistic and bivariate multinomial regressions were employed to model the odds of revision surgery (overall and for specific diagnoses) as a function of surgeon case load. Two-year revision rates, the proportional reduction of the revision burden and the number of patients hypothetically needing treatment reassignment to higher-volume surgeons were simulated for increasing minimum volume standard thresholds. RESULTS: In total, 74,565 total hip arthroplasty procedures performed by 384 surgeons were assessed. The mean surgeon case load was 28.7 total hip arthroplasties / year (min/max: 1.8/269.1; median: 18.1). The average overall 2-year revision rate in the observation period was 2.25%. A higher surgeon case load was associated with lower cumulative revision rates (revision for any reason, and revision due to infection, dislocation and femoral periprosthetic fracture). Overall revision rates of surgeons with a minimal case load of up to 10 / 20 / 50 total hip arthroplasties / year were 2.18% / 2.01 % / 1.70%, respectively. Implementation of a minimum volume standard of 10 / 20 / 50 total hip arthroplasties / year would reduce the overall 2-year revision rates by 3.2%, 10.5% and 23.8%, respectively, but also require that 5.1%, 18.1% and 53.8% of patients be reassigned to higher-volume surgeons instead of initially intended lower volume surgeons. CONCLUSION: A higher surgeon case load independently predicts a lower overall 2-year revision rate in patients undergoing primary total hip arthroplasty for hip osteoarthritis in Switzerland. Implementation of a minimal case load has the potential to significantly reduce 2-year revision rates, at the cost of more patients needing to have their treatment reassigned.